Sex Differences in Pulmonary Eicosanoids and Specialized Pro-Resolving Mediators in Response to Ozone Exposure. (27th June 2021) - Yaeger, Michael J; Reece, Sky W; Kilburg-Basnyat, Brita; Hodge, Miles X; Pal, Anandita; Dunigan-Russell, Katelyn; Luo, Bin; You, Dorothy J; Bonner, James C; Spangenburg, Espen E; Tokarz, Debra; Hannan, Johanna; et al.
Abstract: Ozone (O3 ) is a criteria air pollutant known to increase the morbidity and mortality of cardiopulmonary diseases. This occurs through a pulmonary inflammatory response characterized by increased recruitment of immune cells into the airspace, pro-inflammatory cytokines, and pro-inflammatory lipid mediators. Recent evidence has demonstrated sex-dependent differences in the O3 -induced pulmonary inflammatory response. However, it is unknown if this dimorphic response is evident in pulmonary lipid mediator metabolism. We hypothesized that there are sex-dependent differences in lipid mediator production following acute O3 exposure. Male and female C57BL/6J mice were exposed to 1 part per million O3 for 3 h and were necropsied at 6 or 24 h following exposure. Lung lavage was collected for cell differential and total protein analysis, and lung tissue was collected for mRNA analysis, metabololipidomics, and immunohistochemistry. Compared with males, O3 -exposed female mice had increases in airspace neutrophilia, neutrophil chemokine mRNA, pro-inflammatory eicosanoids such as prostaglandin E2, and specialized pro-resolving mediators (SPMs), such as resolvin D5 in lung tissue. Likewise, precursor fatty acids (arachidonic and docosahexaenoic acid; DHA) were increased in female lung tissue following O3 exposure compared with males. Experiments with ovariectomized females revealed that loss of ovarian hormones exacerbates pulmonary inflammation and injury. However, eicosanoid and SPM production were not altered by ovariectomy despite depleted pulmonary DHA concentrations. Taken together, these data indicate that O3 drives an increased pulmonary inflammatory and bioactive lipid mediator response in females. Furthermore, ovariectomy increases susceptibility to O3 -induced pulmonary inflammation and injury, as well as decreases pulmonary DHA concentrations.